ANALISIS STRATEGI PENINGKATAN KEPATUHAN PENGOBATAN PADA PASIEN TUBERKULOSIS RESISTEN OBAT (TBC-RO) DI INDONESIA - Irwanisyah, Latifa; Hafiz , Nediar; Sitorus, Nosten Saputra; Assifani , Raissa Saifa; Sitorus, Reinhard Paulus; Khumas, Asniar; Tanjung, Riyan Rahmat Ramadhan (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
This study aims to analyze various strategies for improving medication adherence among Drug-Resistant Tuberculosis (DR-TB) patients in Indonesia. Currently, Indonesia ranks second globally in the number of TB cases, with an increasing incidence of DR-TB posing a significant challenge in disease control. Patient adherence to the lengthy DR-TB treatment regimen is influenced by various factors, including family support, education, motivation, and socio-economic factors. This research employs a literature review method by analyzing relevant scholarly articles and journals to identify effective strategies for enhancing treatment adherence. The analysis results indicate that strong family support and good patient motivation are significant factors influencing treatment adherence. Moreover, intervention strategies involving education, psychological counseling, and social support have proven effective in improving patient adherence. This study aims to provide guidance for healthcare professionals and policymakers in designing more effective intervention programs to address the issue of DR-TB treatment adherence in Indonesia.